Modelling the impact of SuDS for stormwater quality management in the Bongani River catchment, Knysna - Van der Merwe, Calvin David (Department of Civil Engineering, 2026)
The Bongani River is a primary pollutant source of stormwater runoff discharging into a shallow portion of the Knysna Estuary known as the Ashmead Channel (Harvey, 2019), situated on the southern coast of South Africa along the Garden Route. The Ashmead Channel is experiencing continuous macroalgal blooms which threaten the ecosystem's biodiversity (Human et al., 2016; Claasens et al., 2020). Furthermore, the recurring algal blooms have impacted – and will continue to impact – the aesthetic appearance and intrinsic value of the ecosystem goods and services provided by this environment (Allanson, 2010). The Herald Reporter (2019) highlighted that SANParks and the public are concerned about pollution and have expressed their desire to improve the quality of stormwater runoff entering the Knysna Estuary. One of the ways to improve the quality of stormwater in the Bongani River is to introduce Sustainable Drainage Systems (SuDS) into the catchment area to aid in improving stormwater management. SuDS aim to achieve holistic management of water quantity and flooding, water quality and surface water pollution, public amenity and community inclusion, and the conservation and protection of biodiversity (Armitage et al., 2013; Woods Ballard et al., 2015). The feasibility of reducing nutrient loads using SuDS was investigated by developing a hydrological model of the Bongani River. The base model, alongside several intervention scenarios, was developed in PCSWMM (Personal Computer Stormwater Management Model). Flow data collected during the study were used to calibrate the base model. Additionally, water quality was integrated into the models using event mean concentration (EMC) wash-off parameters for Total Nitrogen (TN) and Total Phosphorus (TP), which were estimated from an analysis of grab samples. The calibrated model was designated as the Current Scenario and was compared to the following additional scenarios: • Pre-development Scenario – the Current Scenario modified to represent, as closely as reasonably possible, the likely state of the site before human development. • Settlement Upgrade Scenario – incorporating the potential upgrading of the low-income areas to that more akin to typical suburban conditions. • Tributary Management Scenario – incorporating a detention wetland on the western tributary and a retention wetland on the eastern tributary of the Bongani River to manage pollution from the low-income settlements. • Bongani Wetland Upgrade Scenario – incorporating a constructed wetland near the discharge point as a regional control for the entire catchment. The evaluation of the five scenarios was undertaken in two ways: Calvin David van der Merwe MSc. Civil Engineering • In terms of flow quantity which was based on the reduction of flow volume and maximum flow rate in a 20-year timeseries. The Bongani Wetland Upgrade Scenario performed best with reductions of total volume by 77% and maximum flow rate by 71%, with the Settlement Upgrade Scenario and Tributary Management Scenario following, respectively. • In terms of water quality which was based on the theoretical reduction of TN and TP loads over five consecutive 2-year periods. The Bongani Wetland Upgrade Scenario also performed best with reductions of 78% for TN and 77-78% for TP, followed by the Settlement Upgrade Scenario with reductions of TN by 66-75% and TP by 70-74% and the Tributary Management Scenario with reductions of 47-51% for TN and 47-52% for TP. All three of the scenarios achieved the pollutant reduction objectives described in the literature. However, the solutions would need to be combined to achieve the pollutant levels seen in the Pre-development Scenario, which compared with the Current Scenario, was 89% lower for TN and 90% lower for TP.